New horizons of human genetics in digestive diseases - Guoyue Lv (eGastroenterology)
Recent studies have decoded the human Y chromosome sequencing with predominant precision and coverage, offering promising prospects in human genetics and clinical translation. Such an achievement is facilitated by third-generation sequencing technologies including Oxford Nanopore Technology and Pacific Biosciences, which can overcome the limitations of next-generation sequencing. In the context of digestive diseases, these advancements hold significant potential as they can help address the ‘missing heritability’ problem and detect various genomic variants in genetic association analyses, beyond single nucleotide polymorphisms, hoping to reveal ‘major’ genes for complex diseases. Besides, the completion of the Y chromosome enables research into sex-specific genetic effects on diseases and this knowledge can lead to sex-specific therapeutic targets and a better understanding of molecular mechanisms behind gender disparities. In summary, the recent decoding of the Y chromosome, coupled with third-generation sequencing, offers new opportunities to address heritability gaps, discover major disease genes and investigate sex-specific effects in digestive diseases, providing valuable insights for clinicians in delivering precise healthcare services.